Sorghum [Sorghum bicolor (L.) Moench] and cowpea [Vigna unguiculata (L.) Walpers] intercropping improves grain yield, fodder biomass, and nutritive value - Abroulaye, Sanfo; Nouhoun, Zampaligré; Jethro, Delma B.; Abalo, Kulo E.; Abdoulaye, Ouédraogo; Esteban F., Rios; José, Dubeux; Ken, Boote J.; Adegbola, Adesogan (Frontiers in Animal Science, 2023)
Burkina Faso livestock feeding is characterized by a hot dry season fodder deficit, which affects animal performance and causes economic losses. To overcome this challenge, improving quality fodder production through the use of dual-purpose crops is a potential alternative. Hence, this study aimed at testing dual-purpose cultivars of sorghum and cowpea under monoculture and intercropping in North Sudan zone in Burkina Faso. To do this, a "Mother and Baby trials" approach was adopted. The mother trial was designed as a randomized complete block with eight treatments (combinations of monoculture and intercropping systems for two cowpea and two sorghum cultivars) and four replications during two cropping seasons (2019 and 2020) at INERA research station in Saria. The on-farm "baby" trials involved thirty farmers during two cropping seasons (2019 and 2020) in four communes: Koudougou, Poa, Nandiala, and Kokologo. Data were collected on weed biomass and density, fodder biomass and grain yield, intercropping efficiency, and fodder nutritive value. The results of the mother trial showed that intercropping significantly (p≤0.05) reduced weed density and weed biomass. Sorghum cultivar Ponta Negra had the highest fodder biomass yield (10.05 kg DM/ha) while sorghum Sariaso16 had the highest grain yield (4.42 kg/ha). Cowpea cultivar KVx745-11P had greater fodder biomass (4.72 kg DM/ha) than Tiligré (3.28 kg DM/ha) with similar grain yield (2.17 and 2.17 kg/ha). Intercropping was the most efficient land use cropping system for fodder biomass and grain yield improvement both in mother and baby trials. For fodder nutritive value, cultivars Sariaso16 and Ponta Negra had similar crude protein concentration (ranging from 4.1to 5.4%), and cowpea cultivar KVx745-11P haulms had greater crude protein (ranging from 16.9 to 20.3%). Use of Ponta Negra and KVx745-11P, Sariaso16 and KVx745-11P under intercropping is likely to optimize grain and quality fodder production for crop-livestock farmers in North Sudan zone.